A Pragmatic Clinical Trial Approach to Assessing and Monitoring Suicidal Ideation: Results from A National US Trauma Care System Study. Issue 1 (2nd January 2022) - Engstrom, Allison; Moloney, Kathleen; Nguyen, Jefferson; Parker, Lea; Roberts, Michelle; Moodliar, Rddhi; Russo, Joan; Wang, Jin; Scheuer, Hannah; Zatzick, Douglas
Abstract : Objective: Few investigations have comprehensively described methods for assessing and monitoring suicidal ideation in pragmatic clinical trials of mental health services interventions. This investigation's goal was to assess a collaborative care intervention's effectiveness in reducing suicidal ideation and describe suicide monitoring implementation in a nationwide protocol. Method: The investigation was a secondary analysis of a stepped wedge cluster randomized trial at 25-Level I trauma centers. Injury survivors (N = 635) were randomized to control (n = 370) and intervention (n = 265) conditions and assessed at baseline hospitalization and follow-up at 3-, 6- and 12-months post-injury. The Patient Health Questionnaire (PHQ-9) item-9 was used to evaluate patients for suicidal ideation. Mixed model regression was used to assess intervention versus control group changes in PHQ-9 item-9 scores over time and associations between baseline characteristics and development of suicidal ideation longitudinally. As part of the study implementation process assessment, suicide outreach call logs were also reviewed. Results: Over 50% of patients endorsed suicidal ideation at ≥1 assessment. Intervention patients relative to control patients demonstrated reductions in endorsements of suicidal ideation that did not achieve statistical significance (F[3, 1461] = 0.74, P = .53). The study team completed outreach phone calls, texts or voice messages to 268 patients with PHQ-9 item-9 scores ≥1 (n = 161 control, n = 107 intervention). Conclusions: Suicide assessment and monitoring can be feasibly implemented in large-scale pragmatic clinical trials. Intervention patients demonstrated less suicidal ideation over time; however, these comparisons did not achieve statistical significance. Intensive pragmatic trial monitoring may mask treatment effects by providing control patients a supportive intervention. Trial Registration: ClinicalTrials.gov NCT02655354